Theoretically assessed framework for cyberbullying prediction: a study on undergraduate students from universities in Malaysia using pls-sem and neural network approach - Farhan, Bashir (2023)
In the modern era, Information and Communication Technologies (ICTs) have become an integral facet of daily life, enabling both progress and challenges. One prominent challenge is the escalation of cybercrimes like cyberbullying. While ICTs offer numerous societal advantages, they also provide a platform for the propagation of harmful behaviors. Cyberbullying, defined as persistent online abuse intending to harm others, has gained prominence as ICTs have intertwined with academic pursuits, particularly within higher education institutions. Malaysia, like many nations, grapples with the issue of cyberbullying, particularly concerning its youth. The prevalence of cyberbullying among Malaysian young adults raises alarm, given instances of cyberbullying-induced suicides. Cyberbullying ranks as the second most common form of adolescent violence in Malaysia, a statistic underscored by United Nations Children's Fund (UNICEF). A 2021 study by Cybersecurity Malaysia revealed a substantial number of cyberbullying and sexual harassment cases reported to the Malaysian Communications and Multimedia Commission (MCMC) between January 2020 and July 2021, emphasizing the gravity of the issue. While most of the existing cyberbullying studies predominantly focus on teenagers, its impact extends across age groups and becomes increasingly prevalent as individuals grow. In Malaysia, research has concentrated mainly on school-aged children, leaving a significant gap regarding cyberbullying among university students. Consequently, there is a significant gap in understanding the factors that contribute to Malaysian undergraduate university students (MUUS) engaging in cyberbullying. Therefore, it is important to examine and identify these contributing aspects. Thus to address this gap, a representative sample of 428 Malaysian undergraduate students attending public and private institutions in Malaysia was surveyed using an online questionnaire to collect quantitative data. In order to rank the recently identified cyberbullying aspects that could possibly cause MUUS to become cyberbullies, a two-step multi-analytical study technique was employed, which comprised structural equation modelling (SEM) for hypothesis testing and non-compensatory artificial neural network (ANN) analysis. The study found that aggression, anti-social behaviour, and subjective norms significantly influenced the cyberbullying attitudes of MUUS. Conversely, personality, cyberbullying awareness, self-esteem, and internalizing behaviour were insignificant predictors of a cyberbullying attitude. The cyberbullying intention of Malaysian undergraduate university students (MUUS) was found to have significant and positive associations with various factors. These factors include moral disengagement, image, perceived behavioural control (PBC), peer-to-peer relationships, university climate, socioeconomic status, subjective norms, and cyberbullying attitude. The study's findings also indicated that neither parental practises nor the abuse of spouses, siblings, or other family members had a statistically significant impact on respondents' intentions to engage in cyberbullying. The research also revealed a positive moderating relationship between respondents' use of social media and their propensity to engage in cyberbullying. The study has far-reaching implications for researchers, policymakers, parents, and students. By shedding light on the factors that contribute to cyberbullying among undergraduate university students in Malaysia, this research adds valuable new knowledge to the existing literature. The Malaysian government may use the identified criteria to guide policy choices for higher education institutions and encourage National Transformation 2050 (TN50) and a cyberbullying-free learning environment. The results of this study also support SDG No. 16, which aims to promote peace, justice, and stable institutions. Apart from its policy implications, this study holds significant implications for personal morality and the education system. By diminishing the occurrence of cyberbullying, it can contribute to the value and well-being of the education system, fostering healthier mindsets among students. When creating cyber-friendly vii policies, parents and the government can also greatly benefit from having a better understanding of the underlying reasons for cyberbullying. Taking proactive measures to prevent cyberbullying within families and classrooms is crucial for reducing its prevalence among university students. By raising awareness of the negative consequences of cyberbullying, such activities can effectively counteract online abuse and exploitation through social media. This study emphasises the significance of addressing cyberbullying as a serious issue that necessitates a multifaceted and cooperative approach.